Stereospecific alpha-methallylation of hydroxyaldehydes by silatropic ene cyclisation - Robertson, J; Hall, M; Green, S (2009)
We describe the thermal rearrangement of aldehydes bearing an α-(allyl- or crotylsilyl)oxy substituent. The transformations are best described mechanistically as intramolecular silatropic ene reactions based on stereoselectivity, kinetic and computed transition state data. The overall process constitutes a stereospecific (meth)allylation of α-hydroxyaldehydes, under neutral conditions, in which the hydroxyl protecting group is also the (meth)allylating agent. © 2009 Elsevier Ltd. All rights reserved.